Coffee consumption, hypertension, and sleep quality: a cross-sectional study in adult outpatients - Sakti Fadi’a Wijayanti; Luthfiah Nanda; Adzan Fajar Osceola Hafiedz; Rian Ananta Pasolang Seru; Setyo Nugroho; Ronny Isnuwardana (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hypertension is one of the most prevalent non-communicable diseases among the elderly population, while coffee consumption is often associated with increased blood pressure and impaired sleep quality. Objective : This study aimed to analyze the association between coffee consumption, hypertension status, and sleep quality among patients at the general–elderly outpatient clinic of Palaran Primary Health Center, Samarinda Research Methods/ Implementation Methods : This was an observational analytic study with a crosssectional design conducted in September 2025. A total of 137 respondents were selected using a convenience sampling technique, with data collected through questionnaires and analyzed using the Spearman Rank test. Results : The majority of respondents were female (62.8%), with a mean age of 44.47±15.74 years, and a hypertension prevalence of 62.8% (53.3% uncontrolled). The average coffee consumption was 3.21±2.1 cups per week, predominantly instant coffee. Spearman Rank analysis showed no significant association between coffee consumption and hypertension status (p = 0.679), nor with sleep quality (p = 0.525). Conclusion/Lesson Learned : This study concludes that low-to-moderate coffee consumption is not significantly associated with hypertension or sleep quality among adult patients at the outpatient clinic.